Victimisation and Agency: The Social Construction of Union Women's Leadership - Briskin, Linda (Industrial Relations Journal, 2006)
This article interrogates the notion that women union leaders lead differently. Despite significant variation in the union movements in Australia, Canada, Sweden, the UK and the USA, similar discourses on women’s union leadership emerge in all five countries. Based on a materialist social construction approach which supports a recognition of difference without reference to essentialist ideas about women’s nature, this article seeks to identify what may be common across these countries to explain this phenomenon. The article argues that the fact that women face discrimination in unions, on the one hand, and organise as a constituency and have access to women-only education, on the other, supports the development of transformational leadership among women unionists, even across diverse contexts and cultures. Unpacking union women’s leadership practices in this way reveals a dialectic of victimisation and agency.